Early social-cognitive development as a dynamic developmental system—a lifeworld approach - Kärtner, Joscha; Köster, Moritz (Frontiers in Psychology, 2024)
Based on developmental systems and dynamic systems theories, we propose the lifeworld approach—a conceptual framework for research and a hypothesis concerning early social-cognitive development. As a framework, the lifeworld approach recognizes the social embeddedness of development and shifts the focus away from individual developmental outcomes toward the reciprocal interplay of processes within and between individuals that co-constitutes early social-cognitive development. As a hypothesis, the lifeworld approach proposes that the changing developmental system—spanning the different individuals as their subsystems—strives toward attractor states through regulation at the behavioral level, which results in both the emergence and further differentiation of developmental attainments. The lifeworld approach—as a framework and a hypothesis, including key methodological approaches to test it—is exemplified by research on infants' self-awareness, prosocial behavior and social learning. Equipped with, first, a conceptual framework grounded in a modern view on development and, second, a growing suite of methodological approaches, developmental science can advance by analyzing the mutually influential relations between intra-individual and interactional processes in order to identify key mechanisms underlying early social-cognitive development.